Μακαρία η Λέσβος κι η αιώνια πνευματική της άνοιξη - Χατζηαναγνώστου, Τάκης, 1923- ([χ.ό.], 1989)
Μυριβήλης, Στρατής -- Εφταλιώτης, Αργύρης -- Βενέζης, Ηλίας -- Αθανασιάδης, Νίκος -- Μάκιστος, Κώστας -- Πανσέληνος, Ασημάκης -- Ελύτης, Οδυσσέας -- Βαλέτας, Γιώργος -- Παλαιολόγος, Κλεάνθης -- Παπανικόλας, Στρατής